DISTRIBUTION AND SPECIATION OF HEAVY METALS (Cd, Cu AND Ni) IN COASTAL SEDIMENTS OF DUMAI SUMATERA, INDONESIA - Bintal Amin; Ahmad Ismail; Aziz Arshad; M Salleh Kamarudin (JOURNAL OF COASTAL DEVELOPMENT, 2007)
Heavy metal concentrations in sediment collected from Dumai coastal waters have been studied by using sequential extraction technique to determine the distribution and geochemical speciation (EFLE, acid reducible, oxidisable organic and resistant) of Cd, Cu and Ni. The results showed that the highest concentrations of total Cd was in Cargo Port area and the lowest in Penyembal, whilst for Cu and Ni the highest concentrations were in Ferry Port and the lowest in Batu Panjang.  The total concentrations of Cd, Cu and Ni ranged from 0.65 – 1.82, 1.84 – 13.16 and 7.68 – 17.98 µg/g dry weight, respectively. Higher metal concentrations were detected in the eastern and central parts of Dumai city center where most of anthropogenic activities are concentrated. However, most of the concentrations of Cd, Cu and Ni were still below the ERL and ERM values. Only at few stations, especially in the eastern and central parts of Dumai, showed Cd concentrations exceed the ERL but still well below the ERM values. Metal concentrations in 78.26% (Cd) and 91.30% (Cu and Ni) of the sampling stations were dominated by resistant fraction indicating natural origin of these metals. Non resistant fractions, however, were found higher than resistant fractions at Pelintung, Pertamina, Cargo Port, Penyembal and Batu Panjang for Cd; Penyembal and Batu Panjang for Cu and Pelintung and Guntung for Ni. These findings indicated that anthropogenic inputs of Cd, Cu and Ni occurred in these stations. For all sampling site groups, Cd, Cu and Ni were mostly accumulated in the resistant fraction (55.28 – 58.31%; 65.02 – 91.84% and 50.08 – 66.88% of the total concentrations respectively) which indicated that the mobility and anthropogenic inputs of these metals in Dumai coastal waters were quite low.